Exhaled breath temperature in healthy children is influenced by room temperature and lung volume - Logie, K.; Kusel, M.; Sly, P.; Hall, Graham (Wiley-Liss, Inc, 2011)
Background: Exhaled breath temperature (EBT) has been proposed for the non-invasive assessment of airway inflammation. Previous studies have not examined the influence of room temperature or lung size on the EBT. Objective: This study aimed to address these issues in healthy children. Methods: We assessed the effects of room temperature and lung volume in 60 healthy children aged 9–11 years (mean age 10.3 years, 33 male). Static lung volumes were assessed using multiple breath nitrogen washout. Questionnaire and skin prick tests were also used to establish respiratory health in the children. We obtained the EBT parameters of slope, end plateau temperature (PLET) and normalized plateau temperature (nPLET; plateau temperature minus inspired air temperature), and ascertained physiological factors influencing EBT. Results: End plateau temperature was shown to be proportionally affected by room temperature (r = 0.532, P < 0.001) whereas slope and nPLET decreased with increasing room temperature (r = −0.392 P < 0.02 and r = −0.507 P = 0.002). After adjusting for room temperature, height and age, the total lung capacity (r2 = 0.435, P = 0.006) and slow vital capacity (SVC; r2 = 0.44, P = 0.005) were found to be the strongest predictors of end PLET in healthy children. When all factors were included in a multiple regression model, SVC and room temperature were the only predictors of plateau and nPLET. Slope was only influenced by room temperature. Conclusions: Exhaled breath temperature measurements are highly feasible in children with a 95% success rate in this healthy population. Room temperature and SVC significantly influence EBT variables in healthy children. Further studies are required to investigate the ability of EBT to assess airway inflammation in children with respiratory disease.